Growth among HIV-infected Children Receiving Antiretroviral Therapy in Dar es Salaam, Tanzania - Mwiru, Ramadhani S. (Oxford University Press, 2014)
We assembled a prospective cohort of 3144 human immunodeficiency virus (HIV) infected children aged <15 years initiating antiretroviral therapy (ART) in Dar es Salaam, Tanzania. The prospective relationships of baseline covariates with growth were examined using linear regression models. ART led to improvement in mean weight-for-age (WAZ), height/length-for-age (HAZ) and weight-for-length or body mass index (WLZ/BMIZ) scores. However, normal HAZ values were not attained over an average follow-up of 17.2 months. After 6 months of ART, underweight (P < 0.001), low CD4 count or percent (P < 0.001), stavudine containing regimens (P = 0.05) and advanced WHO disease stage (P < 0.001) at ART initiation were associated with better WAZ scores. Age >5 years on the other hand was associated with less increase in WAZ score after 6 months of ART (P < 0.001). These findings suggest that although ART improved the growth of the HIV-infected children in Tanzania, adjunct nutritional interventions may be needed to ensure that the growth of these children is optimized to the greatest extent possible.